(3CUhd GdGbJUGO GdGSdGej (B/s - (3GdeUQj, Qajb jhfSs ((3OeTb(B: s (3OGQ Gdbde(B, s, 1999)
(3ebOeGJ(B-(3GdedcjI GdebjOI(B-(3GdMQjI GdGbJUGOjI hGdJONd(B-(3GdGfJGL(B-(3GdJHGOd(B-(3GdGSJgdGc(B-(3GdJhRjYs
(3HHdhZQGajG U(B.257s
Keywords: (3GdGbJUGO GdGSdGejs; (3Gdabg GdGSdGejs